jurnal TEKNOLOGI TEPAT GUNA “ALAT UKUR KESUBURAN TANAH SEDERHANA” DI KAMPUNG GEMBOR UDIK - Risma Eka Desiyani; Syamsul Bakhri; Putri Sucihati (Jurnal Abdimas Bina Bangsa, 2021)
Soil fertility factors greatly influence success in agriculture, but most farmers still ignore this. One of the factors that cause farmers to fail their crops is artificial fertilizers and other inputs continuously in the long term. The impact of continuous use causes the soil to harden quickly, less able to store water, and promptly becomes acidic, which results in decreased soil fertility. Community service activity aims to increase farmers' knowledge about the application of appropriate technology in the form of a simple, effective and efficient soil fertility measuring device that can be used by farmers to measure the level of soil fertility under management, increase productivity and welfare of farmers and optimize agricultural potential in the local area that it can become one of the food centers.. Community service activities were carried out in Genbor Udik Village sub- district of Cikande , Serangi by the KKM 51 team, The output produced is in the way of a simple, effective and, efficient noun string in measuring soil fertility which, is expected to increase turnover to partners, improve community understanding and skills and increase the quantity and quality of products